Cause and Effect - Intermediate Reading Practice - Ackert, Patricia (Trẻ, 2007)
Cause and Effect, third edition, is an intermediate reading skills text designed for students of English as a second or foreign language who know the basic structures of English and who have a vocabulary od roughly 2.000 English words. The text groups 25 highly engaging reading selections into five themes of unversal interest. Cause and Effect is one a series of three reading skills texts.